Comparing Patterns in Antimicrobial Use During Global Point Prevalence Study at a Single Tertiary Hospital in Ghana: Implications for Antimicrobial Stewardship Programme - Enimil, Anthony; Agbedinu, Kwabena; Yeboah, Michael; Pauwels, Ines; Goossens, Herman; Ansong, Daniel; Mensah, Nicholas; Vesporten, Ann (Frontiers in Tropical Diseases, 2022)
Background The Global Point Prevalence Study (PPS) provides a platform for institutions to register and add clinical information on antimicrobial usage and determine variables related to proper antimicrobial stewardship. Objective To assess the trends in antimicrobial usage and quality indicators in antimicrobial prescriptions at our hospital. Method We retrospectively compared data collected at Komfo Anokye Teaching Hospital (KATH) during the Global PPS in 2015 and 2019. Both surveys took place on a day in September of the respective year. Medical records of all in-patients on admission at 0800 hours on a specific day were reviewed for antimicrobial use in the survey. Data on antibiotic use, including indications for use and the presence of quality indicators, were recorded. Results The total number of patients on admission in 2015 and 2019 were 386 and 630, respectively. The proportion of patients on at least one antimicrobial was 64% (247/386) and 58.4% (368/630) in 2015 and 2019, respectively. Pneumonia was the most common medical condition for which antimicrobial was prescribed for 2015, 30(16.9%) and 2019, 44(23.0%), respectively. There was a decrease in Hospital-acquired infections from 2015, 6.2% (24/386) to 4.8% (30/630) in 2019. The use of biomarkers increased from 4.9% (12/247) to 7.6% (28/368). Conclusion Over 50% of hospitalised patients were on antimicrobials for both years. The inauguration of the antimicrobial stewardship committee at KATH will improve these quality indicators.